2016
DOI: 10.1002/glia.23024
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous distribution of Iba‐1 characterizes microglial pathology in Alzheimer's disease

Abstract: Microglial dystrophy has recently been described as a morphological phenotype of microglia that differs from resting and activated states by spheroid formation and cytorrhexis. In thick sections immunolabeled for HLA-DR or Iba-1 dystrophic microglial processes lose their typical, homogeneous staining pattern and appear to be fragmented or clustered. In this study, we performed double immunofluorescence and electron microscopy to determine if this labeling pattern indeed reflects complete separation of microgli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 68 publications
2
76
0
Order By: Relevance
“…As Iba1 expression may reflect microglial motility (Minett et al, 2016), microglia may be less motile in frontal white matter of GRN mutation carriers. A reduction in Iba1 positive microglia was observed in patients with AD using similar microglial markers (Minett et al, 2016), and Iba1 positive dystrophic microglia are present in AD cases (Streit et al, 2009; Tischer et al, 2016), preceding the spread of tau pathology (Streit et al, 2009). Impaired microglial motility or function within regions such as frontal and temporal white matter could reduce neuronal support, leading to white matter vulnerability in GRN mutation carriers that develop WMH.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As Iba1 expression may reflect microglial motility (Minett et al, 2016), microglia may be less motile in frontal white matter of GRN mutation carriers. A reduction in Iba1 positive microglia was observed in patients with AD using similar microglial markers (Minett et al, 2016), and Iba1 positive dystrophic microglia are present in AD cases (Streit et al, 2009; Tischer et al, 2016), preceding the spread of tau pathology (Streit et al, 2009). Impaired microglial motility or function within regions such as frontal and temporal white matter could reduce neuronal support, leading to white matter vulnerability in GRN mutation carriers that develop WMH.…”
Section: Discussionmentioning
confidence: 89%
“…Three antibodies were used to detect microglia with differing phenotypes, in both ramified and activated states: cluster of differentiation CD68 (CD68), which detects a lysosomal and endolyosomal glycoprotein upregulated in activated, phagocytic microglia; CR3/43, which detects human leucocyte antigen-DR (HLA-DR), a molecule expressed by microglia with antigen presenting cell function and upregulated in inflammation; and ionized calcium-binding adapter molecule 1 (Iba1), which is expressed by resting microglia but upregulated on activated microglia, may reflect microglial motility, and is useful for assessing microglial morphology (Minett et al, 2016; Streit, Braak, Xue, & Bechmann, 2009; Tischer et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…The pathology was characterized by shortened and less branched processes that usually were deformed, displaying cytoplasmic abnormalities (including spheroids) and even fragmentation (cytorrhexis), although this could be due to pathological redistribution of the microglial markers (see also Refs. [54, 57]).…”
Section: Resultsmentioning
confidence: 99%
“…This degenerative process was more prominent in the hilar region of the dentate gyrus and the CA3 region of the hippocampus proper. The microglial pathology is characterized by the following: (1) the presence of degenerative microglial cells, which exhibit shortened and less branched processes, cytoplasmic fragmentation (cytorrhexis) and spheroids formation (see also [54, 57]); (2) a reduction (at least in 4 of 9 Braak V–VI cases tested) in the microglial numerical density; and (3) a dramatic decrease in the area of surveillance of individual microglial cells, described here as the microglial domain. These pathological modifications produce a prominent decrease in the parenchymal area covered by microglia in these particular hippocampal subfields (DG and CA3), leaving most of the parenchymal space with no immune coverage, including Abeta plaques and vascular Abeta depositions.…”
Section: Discussionmentioning
confidence: 99%
“…Altered microglia morphology and reduced arborization have been reported in the human brain during aging and in AD patients (Davies et al, 2016). It remains unclear whether the observed morphological changes are signs of microglia degeneration and a recent study suggests that the reported microglia dystrophy might reflect age-related cytoskeleton alterations (Tischer et al, 2016). Interestingly, direct Tau uptake by microglia has been reported (Bolós et al, 2016) and is enhanced by anti-tau antibodies in an Fc-receptor-dependent manner (Luo et al, 2015).…”
Section: Aging Microglia: Priming Functions and Phenotypesmentioning
confidence: 99%